Model of City Planning Information System Sub Module Building Permits for Klungkung Regency Government - Darma Kotama, I Nyoman; Kessawa Adnyana, Anak Agung Gede Oka; Oka Saputra, Komang (International Journal of Engineering and Emerging Technology, 2019)
To adapt technology trends and work efficiency in public services, Indonesia Government in 2003 started to make a base foundation about how e-government system should be build on the upper government of each regency. Following that law, each regency started to implement their process and services to citizens into their own e-government system. Klungkung regency is a part of Bali Province that still have some parts of its services still going on conventional way, especially on buildings permit. While Klungkung Regency was separated by sea, and has a plan to increase its region documentation, this conventional way sometimes not effective to run. This research will propose a model about building permit system that can be build on top of city planning information system that Klungkung Regency has. Proposed model successfully done with requirements and specification from interview with the authorities, with implementation on user-interface design and technical design on the database